Influence of drying treatments on antioxidant capacity of forage legume leaves - Saw, Yei Sang; Jamharee, Fazrina; Prasad, Krishnamurthy Nagendra; Azlan, Azrina; Maliki, Nurzillah (Springer, 2014)
This study was aimed to investigate the antioxidant capacities of four common forage legume leaves namely, Arachis pintoi (Pintoi), Calapogonium mucunoides (Calapo), Centrosema pubescens (Centro), and Stylosanthes guanensis (Stylo). Two different drying methods (oven-drying and freeze-drying) were employed and antioxidant activities were determined by DPPH, Ferric Reducing Antioxidant Power (FRAP) and β-carotene bleaching assays. Total phenolic content (TPC) was determined using Folin-Ciocalteu assay. Freeze-dried extract showed the highest antioxidant activities by DPPH (EC50 values 1.17–2.13 mg/ml), FRAP (147.08–246.42 μM of Fe2+/g), and β-carotene bleaching (57.11–78.60%) compared to oven drying. Hence, freeze drying treatment could be considered useful in retention of antioxidant activity and phenolic content.